2019 16th Conference on Computer and Robot Vision (CRV) 2019
DOI: 10.1109/crv.2019.00036
|View full text |Cite
|
Sign up to set email alerts
|

aUToTrack: A Lightweight Object Detection and Tracking System for the SAE AutoDrive Challenge

Abstract: The University of Toronto is one of eight teams competing in the SAE AutoDrive Challenge -a competition to develop a self-driving car by 2020. After placing first at the Year 1 challenge [1], we are headed to MCity in June 2019 for the second challenge. There, we will interact with pedestrians, cyclists, and cars. For safe operation, it is critical to have an accurate estimate of the position of all objects surrounding the vehicle. The contributions of this work are twofold: First, we present a new object dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Figure 11 illustrates the aUToTrack pipeline. In Burnett, Samavi, Waslander, Barfoot, and Schoellig (2019), we demonstrated that aUToTrack accurately estimates the position and velocity of pedestrians on both the KITTI Object Tracking benchmark and our own dataset, UofTPed50. We have made this dataset publicly available, and it can be accessed using the link below.…”
Section: Object Detection and Trackingmentioning
confidence: 72%
“…Figure 11 illustrates the aUToTrack pipeline. In Burnett, Samavi, Waslander, Barfoot, and Schoellig (2019), we demonstrated that aUToTrack accurately estimates the position and velocity of pedestrians on both the KITTI Object Tracking benchmark and our own dataset, UofTPed50. We have made this dataset publicly available, and it can be accessed using the link below.…”
Section: Object Detection and Trackingmentioning
confidence: 72%
“…Both the X-zero and the Z-zero algorithms require the LIDAR to be in a parallel position with respect to the road surface. Although this is a common sensor setup [ 34 , 35 , 36 , 37 , 38 , 39 ] and our vehicles were equipped this way, there are notable cases where it is recommended to set it up differently. For instance, [ 38 ] has LIDAR systems both straight (parallel to the road) and tilted.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, dynamic filteringbased tracking that can directly consider the physical movement characteristics is still actively used in various situations. Kalman filter-based tracking algorithms can provide an optimal solution when the motion model is modeled to a linear function [18]- [20]. Extended Kalman Filter (EKF) or Unscented Kalman Filter (UKF) can estimate nonlinear motion models; however, multiple motion models are hard to consider [21]- [23].…”
Section: ) Object Trackingmentioning
confidence: 99%